Oral pemphigus vulgaris in a pediatric patient - Anand R; Jaiswal J; Samadi F (Wolters Kluwer Medknow Publications, 2010)
Pemphigus vulgaris is a chronic autoimmune mucocutaneous disease that initially manifests in the form of intraoral lesions, which spread to other mucous membranes and the skin. The etiology of pemphigus vulgaris is still unknown, although the disease has attracted considerable interest. The pemphigus group of diseases is characterized by the production of autoantibody against intercellular substances and is thus classified as autoimmune diseases. A case of oral pemphigus vulgaris is presented with special emphasis on diagnostic modalities.